2013
DOI: 10.1001/jamainternmed.2013.343
|View full text |Cite
|
Sign up to set email alerts
|

Indications, Complications, and Management of Inferior Vena Cava Filters

Abstract: Importance: Retrievable inferior vena cava (IVC) filters were designed to provide temporary protection from pulmonary embolism, sparing patients from long-term complications of permanent filters. However, many retrievable IVC filters are left in place indefinitely.Objectives: To review the medical records of patients with IVC filters to determine patient demographics and date of and indication for IVC filter placement, as well as complications, follow-up data, date of IVC filter retrieval, and use of anticoagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(85 citation statements)
references
References 21 publications
4
78
0
3
Order By: Relevance
“…Given that a large proportion of rIVCFs remain in situ indefinitely, 3 it is particularly troubling that there have been increasing reports of complications associated with these devices, including filter fracture, migration, organ penetration, and increased risk of deep venous thrombosis. 11,24 In a review of the Food and Drug Administration's own Manufacturer and User Facility Device Experience database, Andreoli et al 25 reported that ≈87% of user-reported adverse events were associated with rIVCFs, as opposed to ≈13% associated with permanent inferior vena cava filters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that a large proportion of rIVCFs remain in situ indefinitely, 3 it is particularly troubling that there have been increasing reports of complications associated with these devices, including filter fracture, migration, organ penetration, and increased risk of deep venous thrombosis. 11,24 In a review of the Food and Drug Administration's own Manufacturer and User Facility Device Experience database, Andreoli et al 25 reported that ≈87% of user-reported adverse events were associated with rIVCFs, as opposed to ≈13% associated with permanent inferior vena cava filters.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In practice, however, the majority of rIVCFs are left in place permanently, with historic retrieval rates as low as 8.5%. [3][4][5] Although poor clinical follow-up of patients with these devices plays an important role, 6 prolonged filter implantation has been associated with retrieval failure rates as high as 43%. [7][8][9][10][11] Furthermore, prolonged rIVCF dwell time is associated with device-related complications, including fracture, migration, organ penetration, and increased risk of deep venous thrombosis.…”
mentioning
confidence: 99%
“…One of the difficulties encountered in removing these types of filters is the extensive neointimal hyperplasia that develops along the struts. Given the relatively short removal window of the OPTEASE filter and the overall low rates of filter retrieval (5), it is likely that a sizeable number of patients are living with OPTEASE and TRAPEASE filters that may no longer be required.…”
mentioning
confidence: 99%
“…Despite recommendations against the use of inferior vena cava filters for venous thromboembolism events and prophylaxis [14,36,39] and clear evidence that they cause thrombosis, the filters continue to be widely used for prevention. Although we did not examine removal rates in this audit, it is also concerning in real-world practice that less than 20% of retrievable filters are actually removed [40]. …”
Section: Discussionmentioning
confidence: 99%